Corneal endothelial cell density and morphology in ophthalmologically healthy young individuals in Japan: An observational study of 16842 eyes - Takashi Ono (Nature Portfolio, 2021)
Abstract We aimed to investigate the cell density and morphology of the corneal endothelium in ophthalmologically healthy young Japanese, given the lack of normative data in literature. This observational study included eyes without ophthalmologic diseases, besides refractive errors, examined between 1996 and 2015 at Miyata Eye Hospital. Eyes with a history of ophthalmologic diseases or contact lens usage were excluded. Correlation of corneal endothelial cell density (ECD), coefficient of variation (CV), appearance rate of hexagonal cells (6A), and cell area with age were examined. Multivariate linear regression analysis was performed to determine the predictors of corneal parameters. We included 16842 eyes of 8421 individuals (19.6 ± 8.7 years). ECD was 3109.0 ± 303.7 cells/mm2 and significantly reduced with age (p < 0.001). The ECD reduction rate was 0.42%/year in the total population. On multivariate analysis, age and sex were significantly correlated with ECD, CV, 6A, and cell area (all p < 0.001). ECD, 6A, CV, and cell area are significantly associated with age in healthy young Japanese individuals. Monitoring their corneal endothelium is essential to assess the risk of endothelial damage.